Coupling regeneration strategy of lithium-ion electrode materials turned with naphthalenedisulfonic acid. (December 2021) - Qiu, Xuejing; Tian, Ye; Deng, Wentao; Li, Fengrong; Hu, Jiugang; Deng, Weina; Chen, Jun; Zou, Guoqiang; Hou, Hongshuai; Yang, Yue; Sun, Wei; Hu, Yuehua; et al.
Highlights: H2 NNS is effective for regeneration of lithium-ion electrode materials. The leaching condition for simultaneous recovery of valuable metals are optimized. Electrode materials with microstructure show excellent electrochemical properties. The principle is potential for recycle of spent battery materials. Abstract: The resource exhaustion and environmental assessment driven by sustainable development make recycle of spent LIBs urgent to be achieved. However, the conventional recycling processes are quite complicated in terms of the tedious steps and secondary contamination. In this paper, hydrosoluble naphthalenedisulfonic acid is firstly proposed to selectively extract valuable metals (Co and Li) for the regeneration of battery materials. Lithium is selectively recovered as lithium enriched solution with a high yield of 99%, while 96.6% cobalt remains in a complex-precipitate benefited from the high acidity and coordination role of naphthalenedisulfonic acid. The leaching of Li fits well with the logarithmic rate law model with an activation energy of 32.42 kJ/mol. Additionally, the regenerated lithium-ion battery active materials (Co3 O4 anode and LiCoO2 cathode) prepared from the cobalt complex-precipitate and lithium-enriched solution exhibit excellent discharged-charged performances and rate capability. This feasible strategy assisted by multifunctional naphthalenedisulfonic acid may offer an alternative option for the simultaneous recovery of Li and Co and the rational resource utilization of spent lithium-ion batteries.